PENGARUH PENGAWASAN TERHADAP DISIPLIN KERJA PEGAWAI PADA KANTOR BADAN PENDAPATAN DAERAH KABUPATEN KUTAI TIMUR - Kaspul pahri (ADMINISTRASI PUBLIK, 2018)
This research is based on supervision conducted by the leadership, in the hope that it can discipline employees in the offices of the regional income office of East Kutai Regency.The purpose of this study is to know to know the influence of supervision of the leadership against the discipline of employees at the office of the regional revenue department of eastern Kutai district. The type of research or explanation used is descriptive kuanlitatif used to analyze the relationship between research variables. Types of data used are kusioner, observation, interview, and documentation.From the results of the research on hypothesis calculation data analysis through t test obtained t arithmetic for Supervisory variables of 3.529 where t count is greater than t table (3.529> 1.684), with R obtained by 0.737, which means that 73.7% discipline employees have pengeruh which is positive against supervis.